Redefining health care : creating value-based competition on results - Porter, Michael E., 1947-; Teisberg, Elizabeth Olmsted (Boston, Massachusetts : Harvard Business School Press, 2006)
En esta obra Michael E. Porter y Elizabeth Olmsted Teisberg presentaron una nueva visión del sistema de cuidado de la salud en el que cada actor se centra en mejorar el valor, medido por los resultados de salud por dólar gastado. [Ellos] prescriben una agenda poderosa y accionable para el cambio. En la competencia disfuncional de hoy, necesita capturar más ingresos, cambiar los costos y los servicios. La competencia tiene lugar en los niveles incorrectos y en las cosas equivocadas. En lugar de obtener buenos resultados provechosos con más pacientes, los administradores hacen esfuerzos costosos e inefectivos para microgestionar los procesos de atención y tomar decisiones secundarias del proveedor. Para reformar el cuidado de la salud, debemos reformar la naturaleza de la competencia misma. --
Introduction (The failure of competition ; Competing on value ; Competing on results ; The structure of this book ; How will redefining health care happen?) -- 1. Scoping the problem -- 2. Identifying the root causes (Positive-sum competition on value ; Zero-sum competition in health care ; The root cause: competition at the wrong level ; Why is health care competition at the wrong level?) -- 3. How reform went wrong (The rise of group health insurance ; Limiting payments to physicians and to hospitals ; Managed care ; The medical arms race ; The Clinton Plan ; Patients' rights ; Consumer-driven health care ; Quality and pay for performance ; A single-payer system ; Medical or health savings accounts ; Non-reforms ; Reforming competition: the only answer) -- 4. Principles of value-based competition (Focus on value, not just costs ; Competition is based on results ; Competition is centred on medical conditions over the full cycle of care ; High-quality care should be less costly ; Value is driven by provider experience, scale, and learning in medical conditions ; Competition is regional or national ; Results information is widely available ; Innovations that increase value are strongly rewarded ; The opportunity of value-based competition)5. Strategic implications for health care providers (The strategy vacuum in health care delivery ; Defining the right goal: superior patient value ; Moving to value-based competition: imperatives for providers ; How would industry structure in health care delivery change? ; Enabling the transformation ; Overcoming barriers to value-based competition ; The benefits of moving early) -- 6. Strategic implications for health plans (Past and future roles of health plans ; Moving to value-based competition: imperatives for health plans ; Overcoming barriers to health plan transformation ; The benefits of moving early) -- 7. Implications for suppliers, consumers and employers (Implications for suppliers ; Implications for consumers as subscribers and patients ; Implications for employers) -- 8. Health care policy. (Broad issues in health case policy ; Moving to value-based competition: improving health insurance and access ; Moving to value-based competition: setting standards for coverage ; Moving to value-based competition: improving the structure of health care delivery ; Implications for health care policy in other nations) -- Conclusion.
Incluye índice.
Bibliogrrafía: páginas 445-488.
Keywords: ATENCION MEDICA -- CONTROL DE CALIDAD; ATENCION MEDICA -- CONTROL DE COSTOS; ATENCION MEDICA -- COSTO-EFECTIVIDAD; ANALISIS DE VALORES (CONTROL DE COSTOS); COMPETENCIA ECONOMICA